The therapeutic potential of three-dimensional multipotent mesenchymal stromal cell spheroids - Petrenko, Yuriy; Syková, Eva; Kubinová, Šárka (Stem cell research & therapy, 2017)
The efficiency of clinical trials involving transplantation of multipotent mesenchymal stromal cells (MSCs) is often insufficient due to harsh conditions present within the target tissue including hypoxia, low nutrient supply as well as inflammatory reactions. This indicates the necessity for optimization of cell-based therapy approaches which might include either modification of the cell manufacturing process or specific cell pretreatment procedures prior to transplantation. Recent reports confirm evidence that the aggregation of MSCs into three-dimensional (3D) multicellular spheroids results in enhancement of the overall therapeutic potential of cells, by improving the anti-inflammatory and angiogenic properties, stemness and survival of MSCs after transplantation. Such an MSCs spheroid generation approach may open new opportunities for the enlargement of MSCs applications in clinical research and therapy. However, the unification and optimization of 3D spheroid generation techniques, including the selection of appropriate clinical-grade culture conditions and methods for their large-scale production, are still of great importance. The current review addresses questions regarding therapeutic-associated properties of 3D multicellular MSCs spheroids in vitro and during preclinical animal studies, with special attention to the possibilities of translating these research achievements toward further clinical manufacturing and applications.
Keywords: Animals; mezibuněčné signální peptidy a proteiny; Pre-clinical studies; Cytokines; Intercellular Signaling Peptides and Proteins; Three-dimensional spheroids; cytokiny; lidé; Multipotent Stem Cells; Therapeutic efficiency; Clinical-grade manufacturing; Cardiovascular Diseases; Spheroids, Cellular; Paracrine activity; kardiovaskulární nemoci; Multipotent mesenchymal stromal cells; Survival; buněčné kultury; Cell Survival; zvířata; Cell Culture Techniques; viabilita buněk; buněčné sféroidy; multipotentní kmenové buňky; Humans